2013
DOI: 10.1002/celc.201300107
|View full text |Cite
|
Sign up to set email alerts
|

Position of Cu Atoms at the Pt(111) Electrode Surfaces Controls Electrosorption of (H)SO4(2)− from H2SO4 Electrolytes

Abstract: Selective positioning of monolayer amounts of foreign atoms at the surface and subsurface regions of metal electrodes is a promising way to fine‐tune the properties of the electrode/electrolyte interface. The latter is critical as it largely governs the adsorption of electrolyte components and reaction intermediates and, therefore, controls many key electrocatalytic processes. Using model Pt(111) single‐crystal electrodes, we demonstrate how the relative position of Cu atoms at the surface drastically changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Unfortunately, none of them is ideal. [33][34][35] Assume the real surface area should be estimated for the unknown Cu-NSA sample by integration of the hydrogen underpotential deposition (or corresponding oxidation) area of the CVs (0.05-0.4 V) taking the value for the unmodified Pt(111) samples as the reference. [31,32] However, the surface coverage by certain species, and consequently the associated charge, depend on the status of the electrode/electrolyte interface.…”
Section: Selection Of Surface-limited Reactions To Estimate the Real mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, none of them is ideal. [33][34][35] Assume the real surface area should be estimated for the unknown Cu-NSA sample by integration of the hydrogen underpotential deposition (or corresponding oxidation) area of the CVs (0.05-0.4 V) taking the value for the unmodified Pt(111) samples as the reference. [31,32] However, the surface coverage by certain species, and consequently the associated charge, depend on the status of the electrode/electrolyte interface.…”
Section: Selection Of Surface-limited Reactions To Estimate the Real mentioning
confidence: 99%
“…Figure 6 A shows the CVs for Pt(111) and a Pt(111) electrode modified by a Cu near-surface alloy (Cu-NSA). [33][34][35] Assume the real surface area should be estimated for the unknown Cu-NSA sample by integration of the hydrogen underpotential deposition (or corresponding oxidation) area of the CVs (0.05-0.4 V) taking the value for the unmodified Pt(111) samples as the reference. While this reaction is commonly used to determine the real surface area of Pt and Pt-alloy electrodes, referring to the unmodified Pt is not suitable in this case.…”
Section: Selection Of Surface-limited Reactions To Estimate the Real mentioning
confidence: 99%
“…Selective positioning of monolayer amounts of foreign atoms at the surface and subsurface regions of metal electrodes is a promising way to optimize the properties of the electrode/electrolyte interface. , In our recent study, we demonstrated that the relative position of Cu atoms at the surface drastically changes the adsorption energies for (bi)­sulfate anions at the Pt(111) interface . Here, we focus on the adsorption of anionic species present in Nafion membranes on Pt(111) and Cu/Pt(111) near-surface alloy (NSA) electrodes and their influence on the ORR kinetics.…”
Section: Introductionmentioning
confidence: 99%